Targeted Mutagenesis, Precise Gene Editing, and Site-Specific Gene Insertion in Maize Using Cas9 and Guide RNA - Svitashev, Sergei (Plant Physiol, 2015)
Targeted mutagenesis, editing of endogenous maize (Zea mays) genes, and site-specific insertion of a trait gene using clustered regularly interspaced short palindromic repeats (CRISPR)-associated (Cas)-guide RNA technology are reported in maize. DNA vectors expressing maize codon-optimized Streptococcus pyogenes Cas9 endonuclease and single guide RNAs were cointroduced with or without DNA repair templates into maize immature embryos by biolistic transformation targeting five different genomic regions: upstream of the liguleless1 (LIG1) gene, male fertility genes (Ms26 and Ms45), and acetolactate synthase (ALS) genes (ALS1 and ALS2). Mutations were subsequently identified at all sites targeted, and plants containing biallelic multiplex mutations at LIG1, Ms26, and Ms45 were recovered. Biolistic delivery of guide RNAs (as RNA molecules) directly into immature embryo cells containing preintegrated Cas9 also resulted in targeted mutations. Editing the ALS2 gene using either single-stranded oligonucleotides or double-stranded DNA vectors as repair templates yielded chlorsulfuron-resistant plants. Double-strand breaks generated by RNA-guided Cas9 endonuclease also stimulated insertion of a trait gene at a site near LIG1 by homology-directed repair. Progeny showed expected Mendelian segregation of mutations, edits, and targeted gene insertions. The examples reported in this study demonstrate the utility of Cas9-guide RNA technology as a plant genome editing tool to enhance plant breeding and crop research needed to meet growing agriculture demands of the future.